A Qualitative Meta-Synthesis of English Education Studies Regarding Development of Taiwanese Students’ Skills in the University Level - Maravilla, Wes Harven G.; Maming, Jimmy Bernabe; Toring, Kimberly N. (Future Science / FSH-PH Publications, 2023)
Technology is crucial to language learning particularly the English language and entails enormous potential. It is also clear that the evolution of technology in the present times has a significant impact on how well foreign language learners acquire their new language. As a result, the current study's objective is to give a meta-synthesis of research findings on student development activities published in prestigious academic journals. Eight 2020–2022 studies examined English language learning innovations. For a systematic review, the studies were grouped using the Critical Skills for Evaluation Program (CASP) checklist and PRISMA 2020 flow diagram. Thematic analysis identified four primary themes were: (1) Using multimedia technology for speaking, (2) Designing and delivering writing courses, (3) Internet-based listening and reading pedagogy, (4) Attending cramming classes. The study's meta-theme, dimensions of a student development activity, emerged. It is advised that teachers and students consider the following aspects of the student development activity in their regular English language study.